Gender Differences in Different Contexts 2017
DOI: 10.5772/65277
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in the Perception of Guilt in Consumer Boycott in Brazil

Abstract: The aim of this chapter is to analyze consumer boycot from the perception of men's and women's guilt on a speciic case involving Nike company through partners in its supply chain in China. The study was conducted with consumers in the city of Rio de Janeiro "razil in . In the process of validating a scale of consumer boycot in "razil, the items of the original scale were kept, but were grouped in diferent factors. The emerged factors were perception of guilt, inluence from others, boycot eiciency, and purchase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 18 publications
(14 reference statements)
0
10
1
Order By: Relevance
“…Fortunately, a few studies investigating boycotts offer useful evidence on how gender difference influences behavioral intention or actual behavior (Cruz et al, 2017;Delistavrou, 2021;Krishna and Kim, 2019;Lindenmeier et al, 2012;Neilson, 2010;Stolle et al, 2005). For example, Cruz et al (2017) found that after receiving negative information about Nike's supply chain abuse, Brazilian women felt more guilty than men, leading to stronger boycott motivations against Nike products. Similarly, while Lindenmeier et al (2012) demonstrated women's stronger inclination to boycott coupled with feelings of outrage, Stolle et al (2005) suggested that women show a higher tendency toward political consumerism (i.e.…”
Section: Hypothesis Development and Research Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Fortunately, a few studies investigating boycotts offer useful evidence on how gender difference influences behavioral intention or actual behavior (Cruz et al, 2017;Delistavrou, 2021;Krishna and Kim, 2019;Lindenmeier et al, 2012;Neilson, 2010;Stolle et al, 2005). For example, Cruz et al (2017) found that after receiving negative information about Nike's supply chain abuse, Brazilian women felt more guilty than men, leading to stronger boycott motivations against Nike products. Similarly, while Lindenmeier et al (2012) demonstrated women's stronger inclination to boycott coupled with feelings of outrage, Stolle et al (2005) suggested that women show a higher tendency toward political consumerism (i.e.…”
Section: Hypothesis Development and Research Modelmentioning
confidence: 99%
“…Although early investigators offered mixed results regarding gender differences, initial insights about the role of gender in predicting consumer boycotts are valuable. While women feel more guilty and uncomfortable than men toward unethical corporate behaviors (Cruz et al. , 2017), affective processes are highly associated with women's (as compared to men's) outrage and boycott intention (Lindenmeier et al.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations